Effect of Ca2+ and Mg2+ cations on surface charges of erythrocytes and lactobacilli Streptococcus thermophilus and their adhesive interaction - Anikieieva, M. A.; Rozanova, S. L.; Kovalenko, S. Ye.; Gordiyenko, O. I.; Gordiyenko, E. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
We propose a simple accessible model of lactobacilli adhesion to human erythrocytes. The effects of divalent (Ca2+, Mg2+) cations on the surface charge of erythrocytes and lactobacilli S. thermophilus and their adhesive interaction have been studied. We have shown that, despite the similar unidirectional influence of Ca2+ and Mg2+ cations on lactobacillus S. thermophilus adhesion to human erythrocytes, the underlying causes of these influences are different. While the Ca2+ ions affect erythrocyte's surface charge but do not change it in S. thermophilus, the Mg2+ ions, on the contrary, influence the lactobacilli surface charge and do not affect the charge of erythrocytes. This result supports the assumption that, in this case, the divalent cations affect the second irreversible stage of the adhesive process rather than the physical interactions of the first reversible stage.